2014
DOI: 10.1016/j.ijrobp.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiation Therapy can Safely and Durably Control Sites of Extra-Central Nervous System Oligoprogressive Disease in Anaplastic Lymphoma Kinase-Positive Lung Cancer Patients Receiving Crizotinib

Abstract: Purpose A preliminary analysis demonstrated that local ablative therapy (LAT) can provide short-term control of extra-CNS (eCNS) lesion progression in tyrosine-kinase addicted non-small cell lung cancer (NSCLC) patients. However, little is known about the long-term efficacy and safety of single and multiple courses of radiotherapy when used to treat these sites of progressive disease. This study analyzes the durability and toxicity of radiotherapeutic LAT applied to eCNS disease progression in ALK+ NSCLC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(104 citation statements)
references
References 21 publications
2
101
0
1
Order By: Relevance
“…The central nervous system (CNS) is a particularly common site of progressive disease in crizotinib-treated patients, suggesting the need for ALKi that not only can overcome acquired crizotinib resistance, but also penetrate the blood-brain barrier (11,12). This review focuses on the use of ceritinib for the treatment of patients with ALK þ , metastatic lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The central nervous system (CNS) is a particularly common site of progressive disease in crizotinib-treated patients, suggesting the need for ALKi that not only can overcome acquired crizotinib resistance, but also penetrate the blood-brain barrier (11,12). This review focuses on the use of ceritinib for the treatment of patients with ALK þ , metastatic lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The use of both SABR and RFA to treat oligoprogression of metastatic lesions in the liver allowed the continued use of ALK inhibitors in our patient for 23 months. It was recently demonstrated that SABR to oligoprogressive sites (1–4 sites) in ALK‐positive NSCLC patients treated with crizotinib enabled continued administration of the ALK inhibitor for a median of 28 months compared with 10.8 months in those cases not treated with ablative therapy 7. Although our patient responded favourably to RFA, its role in metastatic NSCLC treatment needs to be further clarified in larger studies.…”
Section: Discussionmentioning
confidence: 75%
“…In more than half of the patients, no EGFR mutations were found, leading the authors to conclude that the prolonged PFS was attributable to SBRT. Gan et al proposed SBRT for all oligometastatic foci in patients with ALK-rearranged NSCLC in progression during crizotinib, finding no grade 3-5 toxicity, a mean crizotinib therapy duration of 28 months and a 1-and 2-year OS rates of 86 and 57%, respectively (6). Despite these encouraging results, it is still not clear if SBRT for oligoprogressive NSCLC disease could change the natural history of the disease or whether the oligometastatic state represents a manifestation of a less aggressive biological behavior itself.…”
Section: Discussionmentioning
confidence: 99%
“…The standard strategy is to switch to a second-line chemotherapy or, when indicated, to a new-generation TKI. Alternatively, in cases of oligoprogression, especially for asymptomatic cases and brain progression, it is now more and more accepted to continue with the first-line therapy and to treat the new sites of progression with a local therapy, such as radiotherapy (RT) (5)(6)(7)(8)(9). Oligoprogression represents a condition in which a large part of the disease burden is controlled by systemic therapy, except for a few small sites of involvement, which probably acquired resistance to the drug (10).…”
mentioning
confidence: 99%